(untitled) (MAUSAM, 1985)
The analyses of swell observations taken on board Soviet research vessels at two stationary formations period, 16 May to 30 May 1979; and 3 June to 14 June 1979, over Arabian Sea were carried out. The directions of swells north of the equator were affected by westward moving vortices. Directions of swells over the equator seemed’ to be influenced by a system having origin elsewhere. The heights and periods seemed to have been influenced by disturbance coming to the north of the equator from the southern hemisphere in the month of May. The pattern of swell directions showed a clockwise trend associated with increase in height and anticlockwise trend with decrease in height. The onset of monsoon was associated with a clockwise turning of the direction and making them steady westsouthwesterlies.